Method of description of the observed object contour - A. I. Mitsiukhin; I. I. Astrovski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The task is a compact presentation of the contour of the object of observation. The proposed method performs data compression using uncorrelated conversion factors. Method enables data compression without loss. Simplified solution of tasks related to the detection and finding certain objects on images. The results of the evaluation of the effectiveness of encoding image object are shown.